A Search for Radio-loud Quasars within the Epoch of Reionization - Jarvis, M; Rawlings, S; Barrio, F; Hill, G; Bauer, A; Croft, S (Astronomical Society of the Pacific, 2004)
The Universe became fully reionized, and observable optically, at a time corresponding to redshift z~6.5, so it is only by studying the HI and molecular absorption lines against higher-redshift, radio-loud sources that one can hope to make detailed studies of the earliest stages of galaxy formation. At present no targets for such studies are known. In these proceedings we describe a survey which is underway to find radio-loud quasars at z > 6.5.